2020
DOI: 10.1016/j.midw.2020.102775
|View full text |Cite
|
Sign up to set email alerts
|

The impact of covid-19 on midwives’ practice in Kenya, Uganda and Tanzania: A reflective account

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 10 publications
3
61
0
3
Order By: Relevance
“…The world's largest condom manufacturer (Malaysia's Karex Bhd), which produces one in every five condoms in the world, was forced to close in March, thereby limiting the export of condoms [32]. Closure of borders and travel restrictions also affect the distribution of contraceptive medications and devices [33]. A report from the UN regarding the impact of COVID-19 on reproductive health states that national members of the International Planned Parenthood Federation (IPPF) also face commodity and supply shortages, with 59 members reporting delays in moving goods within countries, and 29 facing a shortage of contraceptives [26].…”
Section: Barriers To Access To Contraception In Developing Countries mentioning
confidence: 99%
See 1 more Smart Citation
“…The world's largest condom manufacturer (Malaysia's Karex Bhd), which produces one in every five condoms in the world, was forced to close in March, thereby limiting the export of condoms [32]. Closure of borders and travel restrictions also affect the distribution of contraceptive medications and devices [33]. A report from the UN regarding the impact of COVID-19 on reproductive health states that national members of the International Planned Parenthood Federation (IPPF) also face commodity and supply shortages, with 59 members reporting delays in moving goods within countries, and 29 facing a shortage of contraceptives [26].…”
Section: Barriers To Access To Contraception In Developing Countries mentioning
confidence: 99%
“…Another factor affecting contraceptive provision is the availability of health care workers to physically staff clinics. A study regarding the impact of COVID-19 in Kenya, Uganda, and Tanzania reports that prior to the pandemic, there was a longstanding shortage of health professionals, in addition to overloaded health facilities [33]. As such, midwives play a pivotal role in care provision, by delivering contraception and obstetric care to women and families in remote areas or overwhelmed systems [34].…”
Section: Barriers To Access To Contraception In Developing Countries mentioning
confidence: 99%
“…In Kenya, there have been reports of decreased antenatal attendance, immunisations, and hospital deliveries, along with an increase in stillbirths during COVID-19 [17][18][19]. This decline may be attributable to restricted access to health facilities arising from city lockdowns and curfews imposed by the government, where pregnant women and their companions fear harassment and arrest by the police.…”
Section: Impact Of Covid-19 On Maternal and Newborn Carementioning
confidence: 99%
“…58 Maternal health workers, such as midwives in Kenya, Uganda and Tanzania, reported low numbers attending maternal health clinics, and more women coming into hospitals late, without su cient antenatal care. 59 A survey by the Population Council sampling heads of households across ve Nairobi urban slums found that 9% of participants forewent health services such as antenatal care and immunization/nutrition services for children. 60 Further, a rapid gender analysis by CARE West Africa found consistent reports of false rumors about the virus and a general mistrust of health workers, leading to some men, especially in rural areas, forbidding their wives from seeking health services.…”
Section: Prenatal Carementioning
confidence: 99%